Maximum intensity projection based on high frame rate contrast-enhanced ultrasound for the differentiation of breast tumors - Li, Jia; Wei, Cong; Ma, Xinxin; Ying, Tao; Sun, Di; Zheng, Yuanyi (Frontiers in Oncology, 2023)
We explored the role of maximum intensity projection (MIP) based on high-frame-rate contrast-enhanced ultrasound (H-CEUS) for the differentiation of breast tumors. Methods: MIP imaging was performed in patients with breast tumors who underwent H-CEUS examinations. The microvasculature morphology of breast tumors was assessed. The receiver operation characteristic curve was plotted to evaluate the diagnostic performance of MIP.Results: 43 breast tumors were finally analyzed, including 19 benign and 24 malignant tumors. For the 30 s and >30 s phases, dot-like, line-like or branch-like patterns were significantly more common in the benign tumors. A tree-like pattern was only present in the benign tumors. A crab claw-like pattern was significantly more common in the malignant tumors. Among the tumors with crab claw-like patterns, 3 cases of malignant tumors had multiple parallel small spiculated vessels.There were significant differences in the microvasculature morphology for the 30 s and >30 s phases between the benign and malignant tumors (all p  0.001). The area under the curve, sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of the 30 s phase were all higher than those of the >30 s phase for the classification of breast tumors.MIP based on H-CEUS can be used for the differentiation of breast tumors, and the 30 s phase had a better diagnostic value. Multiple parallel small spiculated vessels was a new finding, which could provide new insight for subsequent study of breast tumors.